The Helmholtz Equation Least Squares Method: For Reconstructing and Predicting Acoustic Radiation - WU, SEAN (Springer, 2015)
This book represents the HELS (Helmholtz equation least squares) theory and its applications for visualizing acoustic radiation from an arbitrarily shaped vibrating structure in free or confined space. It culminates the most updated research work of the author and his graduate students since 1997. The book contains six chapters. The first serves as a review of the fundamentals in acoustics and the rest cover five specific topics on the HELS theory.